2019
DOI: 10.1111/are.14053
|View full text |Cite
|
Sign up to set email alerts
|

The effect of timing of extended photoperiod on growth and maturity of brook trout ( Salvelinus fontinalis )

Abstract: The influence of timing of extended photoperiods on growth and maturity of brook trout was investigated in a 112‐day experiment. The fish with mean initial weight of ~192 g were reared under four light regimes: one control group with natural ambient photoperiod and three groups exposed to an 18L:6D regime initiated at days 1, 23 or 46 of the growth trial. Light‐emitting diodes, with intensity of 250–1000 lux, depending on the distance from the light source, were used for extending light periods. There was a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thus, the effects of photoperiod may vary depending on the physiological conditions of the concerned species and its habitat. GSI is an important index used to evaluate the maturity of fishes, HSI is often used as an indirect indicator of the energy state of animals, and CF indicates the fatness and growth of fishes (Garcia‐Lopez et al ., 2007; Lundova et al ., 2019). The results showed that GSI and HSI showed consistent changes and were higher in the long photoperiod group than in the other two groups, whereas CF was lower; this suggested that the energy might change in fish body began to change from the increase of individual body weight to the process of energy storage and gonadal development.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effects of photoperiod may vary depending on the physiological conditions of the concerned species and its habitat. GSI is an important index used to evaluate the maturity of fishes, HSI is often used as an indirect indicator of the energy state of animals, and CF indicates the fatness and growth of fishes (Garcia‐Lopez et al ., 2007; Lundova et al ., 2019). The results showed that GSI and HSI showed consistent changes and were higher in the long photoperiod group than in the other two groups, whereas CF was lower; this suggested that the energy might change in fish body began to change from the increase of individual body weight to the process of energy storage and gonadal development.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were carried out at Stafila laboratory, České Budějovice, Czech Republic. Male and female fish data were analyzed separately [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the success in developing rearing technologies and the growing market interest, early sexual maturation is a major problem in the on-growing industry. Precocious maturation has a negative impact on the growth rate—mature individuals invest heavily in the development of gonads and show negative growth performance [ 10 , 11 ], the immune system—by inability of producing isohemagglutinins, which can leads to the reduction of bactericidal activity [ 12 ], and product quality—softer fillets with reduced fat and low slaughter yield [ 13 ]. In early puberty, fish show a high growth potential, a factor increasing profitability in the farming industry [ 14 ], but somatic weight subsequently stabilizes or decreases, as resources are diverted to gonad formation and gamete production [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquaculture has widely used photoperiod manipulation to improve productivity (Imsland et al, 2020;Ruchin, 2021). It has been observed in most intensively farmed fish that extended light periods promote somatic growth (Boeuf and Le Bail, 1999;Aride et al, 2021;Li et al, 2022), while extended darkness periods promote gonadal development and maturation (Hermelink et al, 2017;Lundova et al, 2019). Constant light (LL) has been implemented in commercial production in freshwater recirculation aquaculture systems (RAS) of Atlantic salmon smolts (Lorgen-Ritchie et al, 2022;Ytrestøyl et al, 2022).…”
Section: Introductionmentioning
confidence: 99%